Mexican consumer perception of the implementation of artificial intelligence in marketing - Marín Alcalá , Alejandra; Juárez López, Berenice; Ruiz Santoyo, Grace Aileen; Barrera García, María Guadalupe (Ingeniería Solidaria, 2025)
The implementation of Artificial Intelligence (AI) has fundamentally transformed the marketing landscape, offering significant advantages such as enhanced personalization, operational efficiency, and improved customer service. Nevertheless, some uncertainty remains regarding the use of personal data and transparency in AI applications. This research aims to analyze consumer perceptions in La Laguna concerning the integration of AI in marketing strategies, taking into account both its benefits and its ethical and emotional implications. The study employed a descriptive and cross-sectional design, gathering data through a questionnaire administered to 150 residents of the Metropolitan Area of La Laguna, Mexico, aged between 18 and 40. Results indicate that while a majority of consumers acknowledge that AI has enhanced their experience in terms of speed, personalization, and service quality, concerns persist about the algorithmic analysis of their preferences and a lack of clarity regarding the use of cookies and legal terms. Personalized advertising is generally perceived as relevant yet emotionally neutral. Although AI-driven recommendations influence certain purchasing decisions, they do not surpass the trust consumers place in recommendations from close social circles. The study concludes that, although AI adds considerable value to marketing efforts, its widespread adoption depends largely on consumer trust, which can only be fostered through transparent, ethical, and user-centric practices.